ANALYSIS OF THE DETERMINANTS OF ENVIRONMENTAL, SOCIAL & GOVERNANCE (ESG) WITH SENSITIVE INDUSTRY AS A MODERATING VARIABLE IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sunny Angelia Naibaho; Keulana Erwin; Rina Bukit (CV. Radja Publika, 2025)
This study aims to determine the determinants of Environmental, Social & Governance (ESG), with sensitive industry as a moderating variable, in companies listed on the Indonesia Stock Exchange (IDX) from 2022–2024. This research is quantitative which uses secondary data with testing tools in the form of Eviews 12. Sample used was 32 companies which selected with purposive sampling technique. The results indicate that profitability has a positive and significant effect on Environmental, Social & Governance (ESG). Intellectual capital has a negative and significant effect on Environmental, Social & Governance (ESG). Media coverage has a positive and significant effect on Environmental, Social & Governance (ESG). Sensitive industry significantly moderates the effect of profitability on Environmental, Social & Governance (ESG); sensitive industry insignificantly moderates the effect of intellectual capital on Environmental, Social & Governance (ESG) and sensitive industry insignificantly moderates the effect of media coverage on Environmental, Social & Governance (ESG)